Visiting Intention: A Perspective of Destination Attractiveness and Image in Indonesia Rural Tourism - Syahmardi Yacob; Johannes Johannes; Nor Qomariyah (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2019)
The purpose of this study is to investigate the effect of destination attractiveness and image on visiting intention in Indonesia rural tourism. Data were collected from tourist are visiting rural tourism in Kerinci district, Jambi Province (Indonesia). This study used the three variables important factors to develop tourism destination where one of potential object existed, meanwhile destination image from the tourism influenced their interest to visit. The research finding is the significant impact of destination attractiveness through destination image towards development of visiting intention. A main reason destination attractiveness is one of key factors to attract tourist what they want and need. Secondly, an important to create nature tourism achievement perspective between local people and government. Third, also to increase a public awareness of their effort an environment protecting and preserving it as economic value thru rural tourism.